2016
DOI: 10.1016/s2095-3119(16)61368-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of antimicrobial resistance in Staphylococcus aureus isolated from bovine mastitis cases in Northwest China

Abstract: Staphylococcus aureus is the most common etiological pathogen of bovine mastitis. The resistant strains make the disease difficult to cure. The aim of this study was to characterize the genetic nature of the antimicrobial resistance in S. aureus cultured from bovine mastitis in Northwest China in 2014. A total of 44 S. aureus were isolated for antimicrobial resistance and resistance-related genes. Antimicrobial resistance was determined by disc diffusion and the corresponding resistance genes were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 31 publications
8
29
3
3
Order By: Relevance
“…In agreement with other studies, genes encoding for the beta-lactamases blaZ gene were identified in staphylococci at 97% [8,62]. This likely contributed to the high resistance level to penicillin (ampicillin 66.1%) recorded in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with other studies, genes encoding for the beta-lactamases blaZ gene were identified in staphylococci at 97% [8,62]. This likely contributed to the high resistance level to penicillin (ampicillin 66.1%) recorded in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This likely contributed to the high resistance level to penicillin (ampicillin 66.1%) recorded in this study. High blaZ genes might indicate an increased use, and possibly misuse, of β lactams in the study farms [62].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The mastitis of cattle is one of the main origins of MRSA in milk or dairy products. 24,25 Therefore, control and monitoring programs and avoiding utilization of such antibiotics in farms can be considered as essential tasks to combat these infections in human.…”
Section: Discussionmentioning
confidence: 99%
“…Although necessary for both therapeutic and prophylactic purposes, treatment with antibiotics is not fully efficient, and presents several drawbacks. The extended use of antibiotics is at the background of the development of anti-microbial resistance that can persist in the bacterial community [11, 12], as demonstrated for Streptococcus agalactiae [13] and Staphylococcus aureus [14]. Furthermore, the massive use of antibiotics in dairy animals is at the origin of antibiotic residues’ pollution in the environment and contamination of milk and other animal-derived products, causing antibiotic resistance in humans as well [15].…”
Section: Introductionmentioning
confidence: 99%